Dapagliflozin and cardiovascular mortality and disease outcomes in a population with type 2 diabetes similar to that of the DECLARE‐TIMI 58 trial: A nationwide observational study. Issue 5 (6th February 2019) - Norhammar, Anna; Bodegård, Johan; Nyström, Thomas; Thuresson, Marcus; Nathanson, David; Eriksson, Jan W.
Abstract : Aims: To investigate cardiovascular (CV) safety and event rates for dapagliflozin versus other glucose‐lowering drugs (GLDs) in a real‐world type 2 diabetes population after applying the main inclusion criteria and outcomes from the DECLARE‐TIMI 58 study. Methods: Patients with new initiation of dapagliflozin and/or other GLDs were identified in Swedish nationwide healthcare registries for the period 2013 to 2016. Patients were included if they met the main DECLARE‐TIMI 58 inclusion criteria: age ≥40 years and established CV disease or presence of multiple‐risk factors, e.g. men aged ≥55 years and women aged ≥60 years with hypertension or dyslipidaemia. Propensity scores for the likelihood of dapagliflozin initiation were calculated, then 1:3 matching was carried out. DECLARE‐TIMI 58 outcomes were hospitalization for heart failure (HHF) or CV‐specific mortality, and major adverse CV events (MACE; CV‐specific mortality, myocardial infarction, or stroke). Cox survival models were used to estimate hazard ratios (HRs). Results: After matching, a total of 28 408 new‐users of dapagliflozin and/or other GLDs were identified, forming the population for the present study (henceforth referred to as the DECLARE‐like cohort. The mean age of this cohort was 66 years, and 34% had established CV disease. Dapagliflozin was associated with 21% lower risk of HHF or CV mortality versus other GLDs (HR 0.79, 95% confidence interval [CI] 0.69‐0.92) and had no significant association with MACE (HR 0.90, 95% CI 0.79‐1.03). HHF and CV mortality risks, separately, were lower at HR 0.79 (95% CI 0.67‐0.93) and HR 0.75 (95% CI 0.57‐0.97), respectively. Non‐significant associations were seen for myocardial infarction and stroke: HR 0.91 (95% CI 0.74‐1.11) and HR 1.06 (95% CI 0.87‐1.30), respectively. Conclusion: In a real‐world population similar to those included in the DECLARE‐TIMI 58 study, dapagliflozin was safe with regard to CV outcomes and resulted in lower event rates of HHF and CV mortality versus other GLDs.